2020
DOI: 10.3390/w12071952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Indo-Pacific Climate Variability on High Streamflow Events in Mahanadi River Basin, India

Abstract: The potential impact of climate variability on the hydrological regime in the Mahanadi river basin is of great importance for sustainable water resources management. The impact of climate variability on streamflow is analyzed in this study. The impact of climate variability modes on extreme events of Mahanadi basin during June, July, and August (JJA), and September, October, and November (SON) seasons were analyzed, with daily streamflow data of four gauge stations for 34 years from 1980 to 2013 found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…The region is served with water mainly by four rivers, the Dithokeng, Mogalakwena Deep pool (Ngwaditse), Rooisloot and the Dorps Rivers, which supply water for various domestic and irrigation purposes [25]. Sahu et al [26] studied the impact of climatic variability on the streamflow of river; therefore, the study area's climatic data were analyzed to see the rainfall and temperature patterns. There are five sampling sites selected for this study-Mogalakwena Deep pool, Rooisloot downstream and upstream, Dithokeng dam and Dorpsrivier, as shown in Figure 1.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The region is served with water mainly by four rivers, the Dithokeng, Mogalakwena Deep pool (Ngwaditse), Rooisloot and the Dorps Rivers, which supply water for various domestic and irrigation purposes [25]. Sahu et al [26] studied the impact of climatic variability on the streamflow of river; therefore, the study area's climatic data were analyzed to see the rainfall and temperature patterns. There are five sampling sites selected for this study-Mogalakwena Deep pool, Rooisloot downstream and upstream, Dithokeng dam and Dorpsrivier, as shown in Figure 1.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Hence, the risk of flooding is enhanced during La Niña events in the northeast of South Africa. The occurrence of La Niña has also been linked to high/extreme streamflow events in several other regions in the tropics [27][28][29], which increase the risk of riverine flooding. Due to its warm climate, the Limpopo Province is also vulnerable to climate-sensitive diseases such as malaria, which often peak after a flood event.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [22] investigated the middle Mahanadi river basin and discovered signi cant spatiotemporal variation, including seasonal shifts, increasing dry spells, and extreme weather events, to better understand changes in precipitation characteristics and patterns on a regional scale agro-climatic zone. Sahu et al [19] have studied the Mahanadi river basin to explore the combined and relative effect of "Indian monsoon and Indo-paci c climatic modes" on the ood frequency analysis and high stream ow events and found that ENSO and ENSO Modoki were signi cant during JJA and SON on river extremities. Sahu et al [16] have studied the Mahanadi river basin to explore the effectiveness of DBSCAN for precipitation regionalization and found good agreement in clusters, but underestimating the homogeneity characteristics, the ndings were assessed using a popular unsupervised hierarchical cluster analysis.…”
Section: Introductionmentioning
confidence: 99%